PENGARUH BAHAN KIMIA DAN KUALITAS PERALATAN LAUNDRY TERHADAP EFEKTIVITAS KINERJA OPERASIONAL HOUSEKEEPING DI HOTEL NOVOTEL JAKARTA CIKINI - Firas Rahmanikram Susetya; Latif Bagus Syarifuddin (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This research is motivated by the importance of effective housekeeping operational performance in supporting hotel service quality, particularly in laundry activities, which are highly dependent on technical factors such as chemicals and equipment. Frequent problems include inconsistent washing results, process delays, and potential increases in operational costs. Therefore, this study aims to analyze the influence of laundry chemicals and equipment quality on the effectiveness of housekeeping operational performance. This study used a quantitative, survey-based approach. Data were collected through questionnaires from 30 housekeeping employees involved in laundry operations using a saturated sampling technique. Data analysis was performed using multiple linear regression with the help of statistical software (SPSS), and through validity, reliability, and classical assumption tests to ensure model adequacy. The results showed that laundry chemicals (β = 0.421; p < 0.05) and equipment quality (β = 0.367; p < 0.05) had a positive and significant effect on performance effectiveness, contributing 64.6%. Optimizing technical operational factors is crucial for improving housekeeping effectiveness. Further research is recommended to include other variables, such as employee competency and the monitoring system.